Data on investigation of potential gold mineralization sites in Tchollire and Environs (North Cameroon) - Quentin Marc Anaba Fotze; Marcelin Bikoro Bi-Alou; Théophile Ndougsa Mbarga; Jean Paul Sep Nlomngan; Abdoul Aboubakar; Christian Mana Bouba; Ismaila Ahmadou; Alifa Guedala; Lydie Konga; Oussena Nzie (Data in Brief, 2024)
Fresh and altered rock samples were collected and analyzed during field and laboratory studies in Tchollire and Environs. This approach aimed at the delineation of hydrothermal alteration minerals which according to the geological and mining settings of Tchollire and Environs, may be associated with gold mineralizations sites. Field investigations were achieved during the dry season to ensure the representativeness and reliability of our samples whose collections were constrained by earlier remote sensing and geophysical studies as expressed in [1]. An optical microscope both in reflected and transmitted light was used for petrographic analyses of thin and polished sections of rock samples. Other rock samples were prepared for spectral measurements which were achieved using an analytical spectral device spectrometer. The data presented here are further interpreted and discussed in [1].